Answers

  • Brainly User
2014-06-17T15:47:41+05:30
1) x - y =10 ----- (1) 
x + y =10 ------ (2) 
from (1) x = 10 +y 
putting this in (2) 
(10+ y) + y = 10 
i.e 2y =  0 
so y = 0 
from (2) y = 10 - x 
put this in (1) x -(10- x) =10 
so 2x = 20 i.e x = 10 
hence x= 10 y = 0

2)
2x + y = 7 ---------> y = -2x + 7 
substitute y = -2x + 7 in 3x - 2y = 0 
3x - 2(-2x + 7) = 0 
3x + 4x -14 = 0 
7x = 14 
divide each side by 7 
x = 2 
substitute x = 2 in y = -2x + 7 
y = -2 * 2 + 7 = -4 + 7 = 3 
(x, y )= (2, 3) 

3)Sorry, I don't know......
1 5 1
mark my answer as best plz
thanks i will mark it best
okk